Utzon: The defining light of the Third Generation - Carter, Adrian; Sarvimäki, Marja (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
In Space, Time, and Architecture, Sigfried Giedion identified Jørn Utzon as one of the proponents and leaders of what Giedion regarded as the Third Generation of modern architecture in the 20th century. This article considers how Utzon subsequently further exemplified in later works the principles Giedion had identified as essential to that Third Generation and discusses, as Giedion did not explicitly, the significance of light in Utzon’s architecture, which plays a key role in underpinning and articulating these defining principles. This article addresses how the principles Giedion attributed to Utzon and his defining consideration of light, derived from his interpretations of his many transcultural sources of inspiration, notably including from, China, Iran, Japan, Hawaii, Mexico, and Morocco, as well as from his own Nordic realm and Europe, as can be seen in the Sydney Opera House, Can Lis in Mallorca, Melli Bank in Tehran, Kuwait National Assembly, and Bagsværd Church in Denmark, among others.